2012
DOI: 10.1007/s11154-012-9226-4
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial haemostasis and menstruation

Abstract: Under normal physiological circumstances menstruation is a highly regulated, complex process that is under strict hormonal control. During normal menstruation, progesterone withdrawal initiates menstruation. The cessation of menstrual bleeding is achieved by endometrial haemostasis via platelet aggregation, fibrin deposition and thrombus formation. Local endocrine, immunological and haemostatic factors interact at a molecular level to control endometrial haemostasis. Tissue factor and thrombin play a key role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 57 publications
1
30
0
1
Order By: Relevance
“…A highly active fibrinolytic process participates in the regulation of normal menstruation. Large amounts of fibrin and fibrin degradation products are found in the menstrual fluid; in this study, higher D-dimer was found during the early follicular phase, which corresponds to the menstruation phase of the uterine cycle [97,101], suggesting systemic rather than local hyperfibrinolytic activity.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…A highly active fibrinolytic process participates in the regulation of normal menstruation. Large amounts of fibrin and fibrin degradation products are found in the menstrual fluid; in this study, higher D-dimer was found during the early follicular phase, which corresponds to the menstruation phase of the uterine cycle [97,101], suggesting systemic rather than local hyperfibrinolytic activity.…”
Section: Discussionmentioning
confidence: 84%
“…During menstruation, the cessation of bleeding is achieved by platelet aggregation, fibrin deposition and thrombus formation [101]. TF and its binding to circulating FVIIa for the formation of the TF/FVIIa complex is central to the endometrial haemostasis, as in the systemic haemostasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One recent study suggests that warfarin suppresses thrombin generation more efficiently than dabigatran [16]. Because thrombin plays a key role locally in the uterus endometrium in the cessation of menstrual bleeding, the difference in suppression of thrombin generation may explain, although this is speculative, why dabigatran was associated with less AUB than warfarin [17,18] Of note, differences in suppression of other hemostatic mechanisms by dabigatran vs. warfarin may further contribute to the observed differences in the occurrence of our primary endpoint [16]. The mechanism explaining a potentially different effect on menstrual bleeding of FXa inhibitors, notably rivaroxaban, and thrombin inhibitors remains unknown.…”
Section: Resultsmentioning
confidence: 99%
“…Непосредственной причиной кровотечений стано-вятся расстройства сосудистого гомеостаза и репаратив-ных процессов в эндометрии, которые возникают вто-рично при наличии структурной патологии или любых других причин, действующих за пределами эндометрия, и первично при независимой эндометриальной дис-функции [8]. В свою очередь, расстройства сосудистого гомеостаза и репарации обусловливаются многими фак-торами, в числе которых персистирующее воспаление, дисбаланс вазоконстрикторных и вазодилататорных простагландинов (увеличение локального синтеза про-стагландина E 2 и простациклина), активация процессов локального фибринолиза, усиление ангиогенеза с повы-шением плотности сосудов, рост содержания оксида азота (антиагреганта и вазодилататора), ускоренный лизис образующихся во время менструации сгустков крови в результате избыточной продукции активатора плазминогена и др.…”
Section: гормональная контрацепция как метод лечения женщин с аномальunclassified